Effect of ramipril on kidney, lung and heart ACE2 in a diabetic mice model - Vergara, Ander (Mol Cell Endocrinol, 2021)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current coronavirus disease 2019 (COVID-19). The main organ affected in this infection is the lung and the virus uses the angiotensin-converting enzyme 2 (ACE2) as a receptor to enter the target cells. In this context, a controversy raised regarding the use of renin-angiotensin system (RAAS) blockers, as these drugs might increase ACE2 expression in some tissues and potentially increase the risk for SARS-CoV-2 infection. This is specially concerning in diabetic patients as diabetes is a risk factor for COVID-19. METHODS: 12-week old diabetic mice (db/db) were treated with ramipril, or vehicle control for 8 weeks. Non-diabetic db/m mice were included as controls. ACE2 expression and activity were studied in lung, kidney and heart of these animals. RESULTS: Kidney ACE2 activity was increased in the db/db mice as compared to the db/m (143.2% ± 23% vs 100% ± 22.3%, p = 0.004), whereas ramipril had no significant effect. In the lung, no differences were found in ACE2 when comparing db/db mice to db/m and ramipril also had no significant effect. In the heart, diabetes decreased ACE2 activity (83% ± 16.8%, vs 100% ± 23.1% p = 0.02), and ramipril increased ACE2 significantly (83% ± 16.8% vs 98.2% ± 15%, p = 0.04). CONCLUSIONS: In a mouse model of type 2 diabetes, ramipril had no significant effect on ACE2 activity in either kidneys or in the lungs. Therefore, it is unlikely that RAAS blockers or at least angiotensin-converting enzyme inhibitors increase the risk of SARS-CoV-2 infection through increasing ACE2.